Breast epithelial cell proliferation is markedly increased with short-term high levels of endogenous estrogen secondary to controlled ovarian hyperstimulation - Chung, Karine (Springer US, 2011)
Oocyte donors have high serum estradiol (E2) levels similar to the serum levels seen in the first trimester of pregnancy. We report in this article our studies comparing cell proliferation, Ki67 (MIB1), and estrogen and progesterone receptor levels (ERα, PRA, and PRB) in the breast terminal duct lobular units of oocyte donors, women in early pregnancy, and in normally cycling women. Breast tissue and blood samples were obtained from 10 oocyte donors, and 30 pregnant women at 5–18 weeks of gestation. Breast tissue samples were also obtained from 26 normally cycling women. In the oocyte donors: peak E2 (mean ~15,300 pmol/l) was reached on the day before oocyte (and tissue) donation; peak progesterone (P4; mean 36.3 nmol/l) was reached on the day of donation; Ki67 was positively associated with level of E2, and the mean Ki67 was 7.0% significantly greater than the mean 1.8% of cycling women. In the pregnant women: mean E2 rose from ~2,000 pmol/l at 5 weeks of gestation to ~27,000 pmol/l at 18 weeks; mean P4 did not change from ~40 nmol/l until around gestational week 11 when it increased to ~80 nmol/l; mean Ki67 was 15.4% and did not vary with gestational age or E2. Oocyte donors have greatly increased levels of E2 and of breast-cell proliferation, both comparable in the majority of donors to the levels seen in the first trimester of pregnancy. Whether their short durations of greatly increased E2 levels are associated with any long-term beneficial effects on the breast, as occurring in rodent models, is not known.